2020
DOI: 10.1111/jfd.13307
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, characterization and expression analysis of major histocompatibility complex class I alpha gene of pufferfish (Takifugu obscurus)

Abstract: The major histocompatibility complex (MHC) genes play a key role in immune response in vertebrates. In this study, an MHC I alpha homolog gene (PfMHC Ⅰα) from pufferfish (Takifugu obscurus) was identified and its subcellular localization and expression patterns of PfMHC Ⅰα after challenge in vivo and in vitro were analysed. The open reading frame of PfMHC Ⅰα was 1,089 bp in length, encoding 362 aa. The immunofluorescence result revealed that PfMHC Ⅰα was presented on the membrane of lymphocytes. qRT‐PCR analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…In this study, both of them were used to stimulate the lymphocytes of pufferfish, causing the up‐regulation of Pf‐MHC IIα and Pf‐MHC IIβ expression (Figure 7). This finding is consistent with the MHC I expression trend of pufferfish lymphocytes stimulated by pathogens (Fu et al, 2020b), and the trend of MHC IIα expression in Ayu ( Plecoglossus altivelis ) stimulated by pathogens (Li, Ding, et al, 2018; Li, Jiang, et al, 2018). The results suggested that MHC II in pufferfish not only participated in the presentation of endogenous antigens, but also was involved in presentation of exogenous antigens.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, both of them were used to stimulate the lymphocytes of pufferfish, causing the up‐regulation of Pf‐MHC IIα and Pf‐MHC IIβ expression (Figure 7). This finding is consistent with the MHC I expression trend of pufferfish lymphocytes stimulated by pathogens (Fu et al, 2020b), and the trend of MHC IIα expression in Ayu ( Plecoglossus altivelis ) stimulated by pathogens (Li, Ding, et al, 2018; Li, Jiang, et al, 2018). The results suggested that MHC II in pufferfish not only participated in the presentation of endogenous antigens, but also was involved in presentation of exogenous antigens.…”
Section: Discussionsupporting
confidence: 88%
“…The pufferfish is anadromous and distribute in East China Sea, Yellow Sea and Sea of Japan with considerable economic value (Fu, Liu, et al, 2020). In recent years, bacterial diseases have brought a negative impact on the aquaculture industry, including the Gram‐negative bacterium A. hydrophila , the main pathogen of pufferfish (Fu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To understand the relative expression after A. hydrophila infection in vivo, the A. hydrophila (BYK00810) was cultured (Fu et al., 2020). Pufferfish were injected intraperitoneally (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…The total RNA from all samples was extracted with Trizol reagent (Vazyme, China) (Fu et al, 2020), and its quality and concentration were detected using electrophoresis in 1% agarose gel and NanoDrop 2000 spectrophotometer (NanoDrop Technologies, USA) (Kong et al, 2021). Next, RNA was reversely transcribed to cDNA using PrimeScript® RT reagent Kit with gDNA Eraser (Takara, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The β-actin of grass carp was used as housekeeping genes. The target and housekeeping genes were calculated using the 2 −ΔΔCT method (Fu et al, 2020).…”
Section: Qrt-pcr Analysismentioning
confidence: 99%